Pengembangan Media Boneka Pendidikan Seks Bagi Anak Usia Dini di Kebupaten Jember - Luluk , Hadiqotul; Sri Tatminingsih; Widuroyekti, Barokah; Yurike Kinanthy Karamoy; Arifin Nur Budiono (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The high frequency of sexual assault charges against young children in the 5–6 year age group served as the impetus for this study. In order to address this issue, early childhood educators must employ engaging and innovative media to teach young children—those between the ages of five and six—about sexuality. Thus, preschool teachers in schools can benefit from the use of sex education puppet media while educating their kids about sex. The purpose of this study is to evaluate the efficacy of using puppetry to introduce young children (ages 5–6) to early sex education. Children between the ages of five and six participated in the research at Kindergarten Amalia Jember. Research and Development (R&D) is the research methodology employed. Techniques for gathering data include observation and questionnaires. Data analysis with product creation and testing the viability of the product. Based on the material expert's evaluation of every facet, the feasibility test has a total score of 21.00, with an average score of 3.00 in the adequate category. The overall score for the aspects evaluated was 41.00, with an average of 2.70 in the sufficient category, depending on how well-suited media experts are. Based on the sample test results, this indicates that the Sig (2-tailed) value is 0.08 > 0.05, it is determined that the development of puppet media for sex education has been effectively established for kids between the ages of 5 and 6.